TEACHING ENGLISH TO PRE-SCHOOL CHILDREN. METHODS AND TECHNIQUES (Proceedings of International Conference on Educational Discoveries and Humanities, 2022)
At present more and more parents want their children to start learning a foreign language (mostly English) before they go to school. In many kindergartens offer this possibility, some, particularly private ones, offer programs only in English. But these are just rare cases. Most often kindergartens provide an English course for their children as an extra curriculum activity once a week or once in 14 days. But what in fact is this tuition about? What do the children do during an English lesson? How long should the lesson last? These and many other issues about the teaching of English to pre-school children are the purpose of this article.